2022
DOI: 10.1039/d2qm00445c
|View full text |Cite
|
Sign up to set email alerts
|

Copper depletion combined with photothermal therapy suppresses breast cancer

Abstract: Metal ions play an important role in cancer growth, so the chelating agents of metal ions are potential therapeutics for cancer treatment. In this paper, a dye molecule (PY-TBDP) with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…To achieve enhanced therapeutic efficacy, Li et al combined metal chelation and photothermal therapy (PTT) based on a dye molecule (PY-TBDP) containing copper chelation (the derivative of dipicolylamine, PY) and photothermal agent (the derivative of boron dipyrromethene, TBDP). [69] When copper was bound with PY, the fluorescence intensity of TBDP gradually decreased, thus realizing the real-time tracking of copper binding. Under the irradiation of 685 nm laser, there was no significant change in the photothermal activity of TBDP nanoparticles (NPs), PY-TBDP NPs, and PY-TBDP NPs bound with copper.…”
Section: Copper Depletion Therapy Based On Nanomaterialsmentioning
confidence: 99%
“…To achieve enhanced therapeutic efficacy, Li et al combined metal chelation and photothermal therapy (PTT) based on a dye molecule (PY-TBDP) containing copper chelation (the derivative of dipicolylamine, PY) and photothermal agent (the derivative of boron dipyrromethene, TBDP). [69] When copper was bound with PY, the fluorescence intensity of TBDP gradually decreased, thus realizing the real-time tracking of copper binding. Under the irradiation of 685 nm laser, there was no significant change in the photothermal activity of TBDP nanoparticles (NPs), PY-TBDP NPs, and PY-TBDP NPs bound with copper.…”
Section: Copper Depletion Therapy Based On Nanomaterialsmentioning
confidence: 99%
“…Copper is a cofactor of most metalloenzymes or proteins and wildly participates in multiple metabolic processes. An imbalance of copper homeostasis can lead to the malignant progression of tumors. Malignant cells, especially TNBC, have a higher demand for copper because their proliferation, angiogenesis, metastasis, and immune evasion are highly dependent on the signaling pathways related to copper metabolism. ,, Copper-dependent targets have inspired great interest in leveraging copper accumulation or depletion to disrupt these processes. , A previous study has reported a small-molecule inhibitor to block the copper chaperone for attenuating cancer cell proliferation . Intriguingly, removal of intracellular copper ions can intervene in the downstream signaling pathway of the copper chaperone and cause cascaded dysfunction of copper-dependent enzymes, , which is a prospective treatment regimen for TNBC.…”
mentioning
confidence: 99%